Two Motives of Russian Dissident Movement: Background and Literature Antagonism Technologies - Луцевич, Людмила (Poznańskie Studia Slawistyczne, 2014)
In the Russian social thinking, the notion „dissident movement” has appeared twice. For the first time, as a historical and theoretical term in the essay The Dissident (1866) by Nikolay Sokolov, and then, a century later in the autobiographical The Confession of a Dissident (1990) by Alexander Zinoviev. Zinoviev considered „the dissident movement” to be social practices, which allow for social generalization. The first part of the article represents the thinking on the initial stage of dissident movement understanding. The Russian essay writers of the 60s of 19th century analyzed this phenomenon based on the European experience, and connected it with the revolutionary struggle against the government and society to build socialist future for the mankind. In the second part of the article, the „dissident movement” is seen as a trial of a philosopher and sociologist who lived in socialism and communist period, in order to describe the merciless technologies to eliminate an individual from the Soviet intelligent society, in the 60s and 70s of 20th century.